Genetic characteristics predict response to venetoclax plus hypomethylating agents in relapsed or refractory acute myeloid leukemia. (3rd November 2022) - Weng, Guangyang; Zhang, Yu; Yu, Guopan; Luo, Tingyue; Yu, Sijian; Xu, Na; Sun, Zhiqiang; Lin, Dongjun; Deng, Lan; Liang, Xinquan; Xiao, Jie; Zhang, Hongyu; et al.
Abstract: Background: The heterogeneity of relapsed or refractory (R/R) acute myeloid leukemia (AML) leads to no response to venetoclax (VEN)–based therapy in more than half of the patients. Genetic characteristics are considered important predictors for response to treatment in adults with AML. However, the association of genetic characteristics with outcomes receiving VEN‐based therapy is incompletely understood in R/R AML. Objective: To evaluate the efficacy of VEN combined with hypomethylating agents (HMA) and identify the potential genetic predictors of response in R/R AML. Methods: A total of 150 R/R AML patients treated with VEN combined with HMA were enrolled in this retrospective study. Outcomes of the response and overall survival (OS) were analyzed. The predictors of response and OS were analyzed by logistic regression or Cox proportional hazards model. Results: With a median of two (range, 1–4) cycles of therapy, the overall response rate was 56.2%, including 22.0% complete remission (CR), 21.3% CR with incomplete hematologic recovery, 2.0% morphologic leukemia‐free state, and 10.7% partial remission, in which 25 patients achieved measurable residual disease (MRD)–negative response. With a median follow‐up of 11.2 [95% confidence interval (CI), 7.2–14.8] months, 1‐ and 2‐year OS were 46.9% (95% CI, 37.8%–58.1%) and 38.9% (95% CI, 28.7%–52.9%), respectively. Adverse cytogenetics and European Leukemia Net (ELN) risk predicted inferior response to VEN‐based therapy. Mutations in IDH1/2, NPM1, ASXL1, and chromatin–cohesin genes predicted superior response to VEN‐based therapy, whereas mutations in active signaling genes such as FLT3‐ITD and K/NRAS predicted inferior response. Conclusion: VEN combined with HMA was effective with R/R AML patients, and the response to treatment was associated with genetic characteristics. Abstract :